VIRTUAL BORDERS: CAN INTERNATIONAL PUBLIC LAW CONTROL THE METAVERSE? - Rahmonov Jaloliddin (Western European Studies, 2025)
The rapid emergence of metaverse technologies—immersive virtual environments blending augmented reality (AR), virtual reality (VR), blockchain, and persistent digital worlds—poses profound challenges to existing legal orders. Entities, individuals, and activities in the metaverse often transcend physical territorial boundaries and resist traditional notions of jurisdiction, sovereignty, and enforcement. This raises the question: to what extent, and in what form, can international law—rooted in states, territory, and consent—control or regulate behavior and borders in the virtual realm? This article seeks to explore the concept of “virtual borders,” examine the limits of international law in this new domain, and propose normative pathways for governance
Keywords: Metaverse; International Law; Digital Sovereignty